Initial and advanced endoscopic findings of monomorphic epitheliotropic intestinal T‐cell lymphoma in the duodenum: A case report. Issue 1 (1st April 2022) - Fukushima, Masanori; Honda, Tetsuro; Komatsu, Naohiro; Sasaki, Ryu; Ozawa, Eisuke; Miuma, Satoshi; Miyaaki, Hisamitsu; Irie, Junji; Okano, Shinji; Nakao, Kazuhiko
Abstract: Monomorphic epitheliotropic intestinal T‐cell lymphoma (MEITL) is an aggressive malignant digestive system lymphoma. We report the case of a 68‐year‐old Asian woman who was diagnosed with MEITL of the duodenum and small intestine due to intestinal obstruction. MEITL is mainly located in the small intestine, and duodenal lesions are rare. Therefore, the endoscopic appearance of MEITL in the duodenum has been reported in only a few cases. In this case, we observed the initial and advanced endoscopic findings of MEITL in the duodenum. The initial findings were only slight mucosal changes; therefore, careful observation is required to detect early‐stage MEITL.